Importance of fenugreek (Trigonella foenum-graecum L) to smallholder farmers in the case of Eastern and Southern Ethiopia - Rameto Roba; Tariku Simion (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Information on the diversity of landraces, cultivation practices, and feeding habits is necessary to improve the crops through selection and/or hybridization. This study was conducted to generate information to document cropping practices, values, and socio-cultural aspects of fenugreek. A study was conducted in five districts of Oromia and one yem special districts at Southern Nations, Nationalities, and Peoples' Regional States, and data were collected using structured and semi-structured interviews from 144 general and 24 key informants. Assessment of data was conducted through interviews with informants regarding cropping systems of the specific landraces, plant nomenclature of traditional landraces, distinctive criteria of each landrace, and use of fenugreek. R software version 4.1.2 and MS Excel 2010 were used to analyze qualitative data, quantify, sort, determine proportions and draw figures, percentages, means, and tables. The result indicated that Hulbata guracha and Hulbata Dima in Eastern Hararghe and Abesha abish and Orome abish in Yem Special district were reported as popular farmers' cultivars. The farmers named the cultivars mainly based on seed color, seed source, and taste. Sole cropping of fenugreek was more common in Yem special district (65.3%), whereas intercropping with sorghum and Catha edulis (khat) was common in East Hararghe (27.3%) and crop rotation was practiced in both East Hararghe (97.2%) and Yem especial district (88.8%). The farmers in the study area use fenugreek mainly as food in East Hararghe (100%) while in Yem special district used mainly as a spice (100%). This is due to socio-cultural and knowledge differences on the importance of fenugreek in the study area that influence feeding habits, cultivation practice, and uses.